2015
DOI: 10.13102/scb438
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia e modos de polinização e dispersão de Fabaceae em floresta ciliar, Chapada Diamantina, Nordeste do Brasil

Abstract: Resumo -Padrões fenológicos vêm sendo descritos com base na frequência, época e duração dos eventos, e analisados em função de fatores bióticos e abióticos, com os ciclos vegetativos e reprodutivos de espécies vegetais comumente relacionados à precipitação e ao comprimento do dia. Neste trabalho, descrevemos as estratégias fenológicas de 11 espécies de Fabaceae ocorrentes na mata ciliar do rio Lençóis, Chapada Diamantina, estado da Bahia, Brasil, e investigamos a influência dos fatores ambientais sobre os padr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
5
0
2
Order By: Relevance
“…Our hypothesis was therefore partially confirmed, as phenophase intensities were best revealed by quantitative and semi-quantitative data and would, for example, favor interpretations of links with resource availability for pollinators and dispersers (Freitas & Bolmgren, 2008;Souza & Funch 2015). The qualitative method did not generate easily distinguishable intensity peaks.…”
supporting
confidence: 55%
“…Our hypothesis was therefore partially confirmed, as phenophase intensities were best revealed by quantitative and semi-quantitative data and would, for example, favor interpretations of links with resource availability for pollinators and dispersers (Freitas & Bolmgren, 2008;Souza & Funch 2015). The qualitative method did not generate easily distinguishable intensity peaks.…”
supporting
confidence: 55%
“…The few studies based on large tropical families have found that the flowering and fruiting patterns are both seasonal and highly synchronic, as for Rubiaceae (San Martin‐Gajardo & Morellato ; Liuth et al . ), or continuous with low interspecific synchrony, as for Fabaceae (Souza & Funch ) and the fruiting of Myrtaceae (Staggemeier et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…parviflora (Fabaceae, Caesalpinioideae, Mimosoide clade, LPWG, 2017), is an episodic evergreen, hemicryptophytic shrub species that occurs in all regions of Brazil, in various types of vegetation such as Highland Rocky grasslands, Cerrado (lato sensu), riverine forest, gallery forest, seasonally deciduous forest, and seasonally semideciduous forest (Souza, 2015). Flowering and fruiting show a sub-annual pattern with an intermediate duration of up to 5 months (Souza & Funch, 2015). In the study area, C. parviflora begins to bloom at the end of the dry season (October), and fruiting occurs from the beginning of the rainy season in December.…”
Section: Organism Modelmentioning
confidence: 99%
“…For instance, in Pantanal wetland, Calliandra parviflora is a 1.5‐m‐high shrub, commonly found in regions with natural, anthropic, accidental or purposeful fires, and is considered a pasture weed of Brazilian Cerrado that is adapted to periodic flooding (Pott, Pott, & de Souza, 2006; Pott & Pott, 1994). This species is characterized by pods that are readily dehiscent upon maturity, with autochorous seed dispersal near the parent plant (Reis & Sousa, 2014; Souza & Funch, 2015). Hence, fire episodes during the fruiting period of the species can have detrimental effects on the viability and germinability of the enclosed seeds, if the fruits are not good thermal insulators or the seeds are not fire tolerant.…”
Section: Introductionmentioning
confidence: 99%